Relationship between Eating Patterns and Sleep Patterns on the Anemia Status of Class XI Female Students at SMAN 7 Samarinda - Dian Ilmi Fadila; Wiryanto; Riana Pangestu Utami (PT FORMOSA CENDEKIA GLOBAL, 2023)
Based on data from the Samarinda Health Office for 2021 in Harapan Baru Village, the percentage of risk of anemia for young women is (58%). Adolescence is a transition period, therefore eating and sleeping patterns must be appropriate to needs. The aim of this research is to determine the relationship between eating patterns and sleep patterns on anemia status in female students. The research design used a cross sectional approach with a sample size of 45 people. Bivariate data analysis used the Spearman rank test. The results of the study stated that there was a relationship between diet and sleep patterns and anemia status. The ρ value for the diet variable is 0.003 (<0.05), so Ha is accepted with the г value being 0.14. The strength of the correlation is weak in the direction of positive (significant) correlation. The ρ value for the sleep pattern variable is 0.007 (<0.05), so Ha is accepted with the г value being -0.47. The strength of the correlation is quite strong with a negative correlation direction (not significant). There is a relationship between diet and sleep patterns on anemia status with different strength and direction of correlation.